PENGEMBANGAN MEDIA DIORAMA BERBASIS AUDIOVISUAL PADA PEMBELAJARAN IPA MATERI SISTEM PENCERNAAN MANUSIA BERSAMA KELAS V SD NEGERI 1 PURWOASRI - Anggara Teja Arya Kusuma; Dhian Dwi Nur Wenda; Erwin Putera Permana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning media is a media tool that helps achieve learning goals. Educational tools in the form of objects are more often referred to as learning media. Learning media are all tools that can be used to achieve educational goals. The research and development method, namely Research and Development (R&D), is a research method used to produce certain products and test the activity of these products. To produce a product that functions and can be used, the product needs to be tested for product effectiveness. From media expert validation, this media received a score of 84% which was interpreted as very good, while from material experts, this media received a score of 84% with a good interpretation. The practicality questionnaire was filled out by the fifth grade teacher at SDN 1 Purwoasri. Based on the results of the questionnaire, the cumulative results of all scores show 96%. After evaluating the effectiveness of multimedia through test questions, the cumulative results showed that all students obtained an average score of 83. This increase shows that the diorama is very effective in increasing students' understanding of the human digestive system. This shows that this diorama is not only interesting and practical, but also able to have a significant impact on learning, so that it can be a very valuable tool in the educational process.Key words: learning media, audiovisual dioramas, science learning, human digestive system, Class V students.